If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -9 = 2 + 5x Reorder the terms: -9 + 8x = 2 + 5x Solving -9 + 8x = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -9 + 8x + -5x = 2 + 5x + -5x Combine like terms: 8x + -5x = 3x -9 + 3x = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 -9 + 3x = 2 + 0 -9 + 3x = 2 Add '9' to each side of the equation. -9 + 9 + 3x = 2 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = 2 + 9 3x = 2 + 9 Combine like terms: 2 + 9 = 11 3x = 11 Divide each side by '3'. x = 3.666666667 Simplifying x = 3.666666667
| 7x-9=21+5x | | 12e-(19)=7-e | | (9x-3)=(3x+6) | | 6cos(x)+8sin(x)=5 | | y(y-6)=16 | | 5x^2-9=12x | | 7/5x=49 | | 3(6y+7)+7y= | | f(x)=(x-3)(2x+6) | | Ax-3x=5forx | | 8y-(3+4y)= | | m=4Gz | | 4x^2+7=-11x | | Ac-3x=5 | | 9/10()=18 | | 8v^2=56v | | Ax-3x=c | | 7g-15=41 | | x^3+3x^2-6x+12=0 | | 144-3x=180 | | x^3-3x^2-6x+12=0 | | 9x^2-12x+62=0 | | x*11+11=x*5+83 | | 8r^2+4r-6=0 | | 2(u-9)-4=-2(-9u+6)-u | | 2(4u+9)=14 | | x+2x=11x | | 12d+3=6d+45 | | 3x^2+16x-35=o | | 4(x-2)=6.4 | | 8(a+1)=84 | | 5=2x+b |